2018
DOI: 10.1007/s12298-018-0566-8
|View full text |Cite
|
Sign up to set email alerts
|

Expression and DNA methylation of SERK, BBM, LEC2 and WUS genes in in vitro cultures of Boesenbergia rotunda (L.) Mansf.

Abstract: The process of somatic embryogenesis and plant regeneration involve changes in gene expression and have been associated with changes in DNA methylation. Here, we report the expression and DNA methylation patterns of - (), (), () and () in meristematic block of newly emerged shoots from rhizome, embryogenic and non-embryogenic calli, prolonged cell suspension culture, ex vitro leaf, and in vitro leaf of regenerated plants of . Among all seven samples, based on qRT-PCR, the highest level of expression of and was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 70 publications
0
27
0
2
Order By: Relevance
“…A decreased 5mC level has been found in the promotors of LEAFY COTYLEDON1 (LEC1) and WUS, respectively, in an embryogenic culture of D. carota [142] and during shoot organogenesis in Arabidopsis [131,143]. Similarly, a decreased methylation level has been reported in the SOMATIC EMBRYOGENESIS RECEPTOR-LIKE KINASE (SERK), LEC2, and WUS genes in the embryogenic calli of Boesenbergia rotunda [144]. Hypomethylation at the CHH sites in a promoter has been associated with the activation of some hormone related and WOX genes in G. hirsutum SE [126].…”
Section: Dna Methylationmentioning
confidence: 84%
“…A decreased 5mC level has been found in the promotors of LEAFY COTYLEDON1 (LEC1) and WUS, respectively, in an embryogenic culture of D. carota [142] and during shoot organogenesis in Arabidopsis [131,143]. Similarly, a decreased methylation level has been reported in the SOMATIC EMBRYOGENESIS RECEPTOR-LIKE KINASE (SERK), LEC2, and WUS genes in the embryogenic calli of Boesenbergia rotunda [144]. Hypomethylation at the CHH sites in a promoter has been associated with the activation of some hormone related and WOX genes in G. hirsutum SE [126].…”
Section: Dna Methylationmentioning
confidence: 84%
“…Reversed phase-high performance liquid chromatography (RP-HPLC) provides robust data on DNA methylation changes affecting the whole genome, but the method may not detect many subtle phenomena (Machczy艅ska et al 2014a). Bisulfite sequencing was tested recently, and provided promising results on tissue culture-induced variation in Boesenbergia rotunda (Karim et al 2018) and sugar beet (Zakrzewski et al 2017). Diversity arrays technology sequencing methylation analysis (DArTseqMet, developed by Diversity Arrays Technology, https ://www.diver sitya rrays .com/techn ology -and-resou rces/darts eq/) is a promising technology for methylation analysis, although it is relatively costly for routine analysis.…”
Section: Introductionmentioning
confidence: 99%
“…DNA methylation plays a vital role in cell dedifferentiation, redifferentiation and the growth and development of plants [ 56 ]. In SE, DNA methylation regulates and maintains the gene expression programs of several genes; however, due to the previously reported critical implications for the embryogenic process in plants, a group of genes has been especially studied ( Figure 1 ): Leafy Cotyledon 1 ( LEC1 ), Wuschel ( WUS), Somatic Embryogenesis Receptor Kinase ( SERK ), Pickle ( PKL ) and Baby Boom ( BBM ) [ 20 , 23 , 57 ]. For instance, the manipulation of methylation in specific genes, such as LEC1 [ 58 ] and Wuschel ( WUS ) [ 59 ], drastically affects the regulation of the differentiation of plant explants.…”
Section: Dna Methylation: a Key Player During Somatic Embryogenesimentioning
confidence: 99%
“…In Boesenbergia rotunda (L.) Mansf., the expression of the SERK , BBM , LEC2 and WUS genes was studied, and also the gene-specific methylation by bisulfite sequencing data of these genes. Based on these results, it was suggested that relatively higher expression and lower level of DNA methylation of SERK , BBM , LEC2 , and WUS are associated with somatic embryogenesis and plant regeneration [ 23 ]. Recently it was reported in cotton that the inhibition of methylation by the use of zebularine activated the transcription of hormone-related genes ( IAA14 , CKX6 , LBD1/3 , LOX1 , CRF4.1 ) and may promote SE [ 33 ].…”
Section: Dna Methylation: a Key Player During Somatic Embryogenesimentioning
confidence: 99%
See 1 more Smart Citation